Synthesis and characterization of PVA-Metal complex composites for electrochemical double layer capacitor (EDLC) devices - Brza, Mohamad Ali (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
In the current work, the preparation of the polymer electrolyte (PE) systems consists of PVA polymer matrix, ammonium thiocyanate (NH4SCN) as ionic source, Cu(II)-, Ce(III)-, and Cd(II)-complex as metal-complexes and glycerol as plasticizer are performed by solution cast technique. The polymer electrolytes are used for application in electrochemical double-layer capacitor (EDLC) device. Due to poor optical, electrical, and electrochemical properties of PVA, it is integrated with the metal-complex and glycerol to increase amorphous phase, electrical conductivity, and decrease optical band gap for the electrolyte to be used for fabricating EDLC device with very high performance. X-ray diffraction (XRD) has shown that the highest conducting plasticized electrolyte with Cu(II)-complexes possess the lowest degree of crystallinity. The possible interactions within the PE elements are verified using Fourier transform infrared (FTIR) spectroscopy. The FESEM images reveal that the surface morphology of the samples showed a uniform smooth surface at high glycerol concentration. This is in good agreement with the XRD and FTIR results. The highest conducting plasticized electrolyte without metal-complexes is found to be 1.82 × 10-5 S cm-1 while the conductivity increased up to 2.25 × 10-3 S cm-1 by the addition of Cu(II)-complex into the PE. The conductivity is found to be affected by the ionic mobility (µ), diffusion coefficient (D), and number density (n) of ions. From UV-Vis spectroscopy study, the optical parameters (absorption edge, refractive index (N), dielectric constant (εr), dielectric loss (εi), and optical band gap energy (Eg)) of pure PVA and composite films are measured. Examination of the εi optical parameter is carried out to measure the Eg, while types of electronic transition in the films are determined based on the Tauc's method. From transference number measurement (TNM), ions are considered as the dominant charge carrier and the transference number for ions and electrons for the highest conducting electrolyte (PGNC-4) are 0.971 and 0.029, respectively. PGNC-4 is electrochemically stable up to 2.15 V. Galvanostatic charge-discharge (GCD) measurement of the EDLC has been supported with cyclic voltammetry (CV) analysis. CV curves are determined by inserting the plasticized electrolytes between two activated carbon (AC) electrodes, and it shows a nearly rectangular shape at low scan rates. The specific capacitance and energy density of the EDLC for the highest conducting plasticized electrolyte with Cu(II)-complexes (PGNC-4) are nearly constant within 1000 cycles at a current density of 0.5 mA/cm2 with average of 155.322 F/g and 17.473 Wh/Kg, respectively. The energy density of the EDLC in the current work is in the range of battery energy density. The EDLC performance was found to be stable over 1000 cycles for the PGNC-4 system. The low value of equivalent series resistance shows that the EDLC has good electrolyte-electrode contact. The EDLC for the PGNC-4 system exhibited the initial high power density of 4.960 × 103 W/Kg.